0657 Impact of Treatment With Mandibular Advancement Oral Appliance on Respiratory Parameters, Sleep and Cardiometabolic Risk Factors of CPAP Non-Adherent Patients With Severe Obstructive Sleep Apnea. (27th May 2020) - Giannasi, L; Gomes, M; Oliveira, L; Nacif, S; Oliveira, E; Rezende, T; Dutra, M; Bacigalupo, E; Soviero, L; Nazário, L; Oliveira, W; Rode, S; et al.
Abstract: Introduction: Obstructive sleep apnea (OSA) may trigger systemic changes linked to important cardiometabolic risk factors such as hypertension, stroke and diabetes II. As a life-threatening, multifactorial disorder, OSA demands a multiprofessional approach. The most common worldwide treatments are Continuous Positive Airway Pressure (CPAP) and Mandibular Advancement Oral Appliance (OAm). The aim of this study was to evaluate the impact of OAm treatment on CPAP non-adherent patients with severe OSA, comparing objective and subjective data between baseline and follow up. Methods: A prospective study was carried out including non-adherent severe OSA patients, which were referred to OAm therapy evaluation. Patients presenting with snoring, gasping/choking during sleep, fatigue and daily sleepiness were evaluated by a sleep medicine specialist and the diagnosis of severe OSA with a basal polysomnography (PSG). All the patients were treated with a standard OAm (PMPositioner®). Baseline and Follow up (6 months) sleep parameters (PSG and Epworth Sleepiness Scale - ESS) were compared to assess treatment efficacy. Results: Seventeen patients (9 with hypertension and 8 with hypertension + diabetes) met the inclusion criteria and 13 finished the protocol. After treatment with OAm the following parameters improved significantly: OSA severity (44.5±13.5 to 9.0±4.3, p≤0.001), ODI (46.8±11.6 to 12.1±9.1(p<0.05)), REM (18.4± 4.8 to 21.5± 2.9 (p<0.05)) and SaO2nadir (75.7± 9.4 to 87.0±3.6, p<0.001), ESS (p<0.005). Ten patients (58%) reported a reduction either in systolic and diastolic blood pressure with 3 of them (30%) reduced the hypertensive drug dose. Conclusion: Our findings show that OAm is a safe and effective treatment option to CPAP non-adherent severe OSA patients. Furthermore OAm therapy had also a positive impact on cardiometabolic risk factors which are particularly relevant outcomes in OSA patients. Support: State of Sao Paulo Research Support Foundation (FAPESP).